(untitled) (Baghdad Science Journal, 2025)
In this work , the effect of chlorinated rubber (additive I), zeolite 3A with chlorinated rubber (additive II), zeolite 4A with chlorinated rubber (additiveIII), and zeolite 5A with chlorinated rubber (additive IV), on flammability for epoxy resin studied, in the weight ratios of (2, 4, 7,10 & 12%) by preparing films of (130x130x3) mm in diameters, three standard test methods used to measure the flame retardation which are ; ASTM : D-2863 , ASTM : D-635 & ASTM : D-3014. Results obtained from these tests indicated that all of them are effective and the additive IV has the highest efficiency as a flame retardant.